P PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI EFEK RUMAH KACA KELAS IV SEKOLAH DASAR - Ningtyas, Claudia Dwi; Pranata, Rio; Miranda, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research and development was to produce a valid animated video learning medium for the "Greenhouse Effect" science subject for fourth-grade elementary school students. The approach used was Research and Development with the ADDIE model, limited to the development stage only. This media development was conducted to address the need for innovative and engaging learning media to deliver material that is difficult for students to understand. Data analysis included qualitative descriptions from interviews, validator input, and product suggestions, as well as quantitative data from needs analysis, expert validation questionnaires, and teacher and student response questionnaires. The analysis results showed an average validity of 87.5% for the material aspect (very valid) and 90% for the media aspect (very valid). These results were supported by teacher responses of 94% (very good) and student responses of 89.65% (very good). Therefore, it can be concluded that the developed animated video is suitable for use as a learning medium.